2017
DOI: 10.1002/sej.1265
|View full text |Cite
|
Sign up to set email alerts
|

The Problems with and Promise of Entrepreneurial Finance

Abstract: Research summary This article provides a review of the entrepreneurial finance literature in the surprisingly not very well integrated entrepreneurship and finance journals. Entrepreneurial finance encompasses venture capital, private equity, private debt, trade credit, IPOs, angel finance, and crowdfunding, among other forms of finance. We analyze trends in citation activity to these topic areas across 16 journals that publish at least somewhat regularly on these topics, and we show there has been a rise in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 72 publications
1
75
0
1
Order By: Relevance
“…In addition to human capital, a critical resource for entrepreneurial firms relates to access to finance. In the final article of the special issue, Doug Cumming and Sofia Johan () examine the surge of interest in this area of research through trends in citation activity in entrepreneurial finance. They highlight an important segmentation that divides the literature between the finance and entrepreneurship/management fields and identify significant research opportunities from bringing these fields together to explore new forms of entrepreneurial finance such as crowdfunding and co‐investment by different types of finance providers.…”
mentioning
confidence: 99%
“…In addition to human capital, a critical resource for entrepreneurial firms relates to access to finance. In the final article of the special issue, Doug Cumming and Sofia Johan () examine the surge of interest in this area of research through trends in citation activity in entrepreneurial finance. They highlight an important segmentation that divides the literature between the finance and entrepreneurship/management fields and identify significant research opportunities from bringing these fields together to explore new forms of entrepreneurial finance such as crowdfunding and co‐investment by different types of finance providers.…”
mentioning
confidence: 99%
“…An interesting review that looks at the research output focused on the period of the VCs postinvestments comes from Manigart and Wright (2013a). Among the most recent attempts to systematize research on the equity investment for startups in several different aspects (e.g., Kaplan and Strömberg, 2009;Metrick and Yasuda, 2010;Kerr and Nanda, 2011;Cumming and Johan, 2017;Wallmeroth et al, 2018), one study which is close in spirit to the present work is Lerner and Tåg (2013). In this case, while authors enquire about the institutional causes that may lead to the development of VC, they confine their analysis to the comparison between the USA and Sweden, without enlarging their perspective and analysing evidence produced in other institutional contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these databases also give rise to several biases, including a statistical bias due to differences in variable definitions (e.g., the definition of VC is not always consistent across countries) and collection methods (Cumming et al, 2009b) thereby sometimes under-representing specific types of investments such as early-stage and small VC investments, or specific countries. These databases also lack control groups of companies that either did not search for (international) VC but have similar characteristics as firms that did, or tried to obtain such financing but were unsuccessful (Cumming and Johan, 2017). Previous work has shown that the use of different international datasets can provide different answers to research questions (Cumming et al, 2014), which might explain some of the contradictory findings.…”
Section: Methodological Issuesmentioning
confidence: 99%